2020
DOI: 10.3847/2041-8213/ab7823
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Evolution of Volatile CO from the Protostellar Disk Stage to the Protoplanetary Disk Stage

Abstract: Recent observations show that the CO gas abundance, relative to H 2 , in many 1-10 Myr old protoplanetary disks may be heavily depleted, by a factor of 10-100 compared to the canonical interstellar medium value of 10 −4 . When and how this depletion happens can significantly affect compositions of planetesimals and atmospheres of giant planets. It is therefore important to constrain if the depletion occurs already at the earliest protostellar disk stage. Here we present spatially resolved observations of C 18 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
73
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 56 publications
8
73
0
Order By: Relevance
“…It is likely that these sources are depleted in CO by about an order of magnitude compared to ISM levels. We note that Zhang et al (2020) recently found evidence for ISM-like CO abundances in three protostellar disks, which may signify that a range of depletion timescales and outcomes are possible. Indeed, chemical models by Drozdovskaya et al (2014) demonstrate that differences in infall physics can strongly influence the chemical processing that occurs in embedded disks.…”
Section: Evolution Of C 18 O Abundancesmentioning
confidence: 60%
See 4 more Smart Citations
“…It is likely that these sources are depleted in CO by about an order of magnitude compared to ISM levels. We note that Zhang et al (2020) recently found evidence for ISM-like CO abundances in three protostellar disks, which may signify that a range of depletion timescales and outcomes are possible. Indeed, chemical models by Drozdovskaya et al (2014) demonstrate that differences in infall physics can strongly influence the chemical processing that occurs in embedded disks.…”
Section: Evolution Of C 18 O Abundancesmentioning
confidence: 60%
“…C 18 O emission has been found to be optically thick in several embedded disks (van 't Hoff et al 2018;Zhang et al 2020). The C 18 O 2-1 optical depths in the embedded disks in Zhang et al (2020) are likely around ∼4-8, based on the reported C 18 O and 13 C 18 O fluxes and assuming a 12 C/ 13 C ratio around 70. We therefore expect that moderate optical depth effects may affect the protostellar sources in our sample.…”
Section: O Abundances Vs Agementioning
confidence: 99%
See 3 more Smart Citations